Rational design of nano-Fe3O4 encapsulated in 3D honeycomb biochar for enhanced lithium storage performance. (27th October 2021) - He, Dafang; Sun, Mufan; Cao, Da; He, Guangyu; Chen, Haiqun
Abstract: Developing green materials applied in lithium-ion batteries is of significant importance for the present-day society. Herein, a feasible strategy to construct Fe3 O4 nanoparticles (NPs) embedded in three-dimensional (3D) honeycomb biochar derived from pleurotus eryngii was proposed. The obtained material consists of Fe3 O4 NPs (35–85 nm) encapsulated in 3D honeycomb biochar possesses a high specific capacity of 723 mAh g −1 at 1.5 A g −1 after 1000 cycles. The effectively enhanced cycling life of Fe3 O4 @C nanocomposites can be ascribed to the small Fe3 O4 NPs provide lower degree of cracking and high specific capacity, while the honeycomb biochar function like a cage to inhibit huge volume change of Fe3 O4 NPs during the charge–discharge process.